Case Report: Systemic Sclerosis After Covid-19 Infection - Fineschi, Serena (Frontiers in Immunology, 2021)
We are reporting a case of systemic sclerosis onset 3 weeks after a confirmed mild Covid-19 infection. A 47-year-old man with no history of any autoimmune diseases and in good health became sick together with his family on the 12th of November with mild symptom: tiredness, fever, cough and sore throat. Oropharyngeal swab for SARS-CoV-2 tested positive. While the other members of his family quickly recovered, he still felt tired 3 weeks later. He came to the emergency room with the following symptoms: fatigue, abdominal pain and vomiting, cutaneous generalised rash with diffuse erythema and a burning skin sensation. Moreover, he had swelling of the eyelids and conjunctivitis. His ESR and CRP were normal. After another two weeks he also presented with dysphagia and white fingertips. The skin rash had disappeared, however he still had periorbital oedema and red eyes as well as the burning sensation in his skin, above all in the fingertips and around the mouth. ANA showed a strongly positive nucleolar pattern. Anti PM/Scl 75 and PM/Scl 100 were positive. Echocardiography showed normal systolic artery pressure, spirometry was normal. After one and a half months HCRT showed incipient interstitial lung fibrosis. Conclusion: SARS-CoV-2 may trigger autoimmunity, in this case systemic sclerosis.